Enhanced field electron emission from aligned diamond-like carbon nanorod arrays prepared by reactive ion beam etching. (13th April 2016) - Zhao, Yong; Qin, Shi-Qiao; Zhang, Xue-Ao; Chang, Sheng-Li; Li, Hui-Hui; Yuan, Ji-Ren
Abstract: Homogeneous diamond-like carbon (DLC) films were deposited on Si supports by a pulsed filtered cathodic vacuum arc deposition system. Using DLC films masked by Ni nanoparticles as precursors, highly aligned diamond-like carbon nanorod (DLCNR) arrays were fabricated by the etching of inductively coupled radio frequency oxygen plasma. The as-prepared DLCNR arrays exhibit excellent field emission properties with a low turn-on field of 2.005 V μ m −1 and a threshold field of 4.312 V μ m −1, respectively. Raman spectroscopy and x-ray photoelectron spectroscopy were employed to determine the chemical bonding structural change of DLC films before and after etching. It is confirmed that DLC films have good connection with Si supports via the formation of the SiC phase, and larger conductive sp 2 domains are formed in the as-etched DLC films, which play essential roles in the enhanced field emission properties for DLCNR arrays.